2013
DOI: 10.4048/jbc.2013.16.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions with a High Intraoperative Expander Fill Volume Increase the Risk for Mastectomy Flap Necrosis

Abstract: PurposeProsthetic-based breast reconstruction is performed with increasing frequency in the United States. Major mastectomy skin flap necrosis is a significant complication with outcomes ranging from poor aesthetic appearance to reconstructive failure. The present study aimed to explore the interactions between intraoperative fill and other risk factors on the incidence of flap necrosis in patients undergoing mastectomy with immediate expander/implant-based reconstruction.MethodsA retrospective review of 966 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Although this may allow for better skin recruitment, some studies suggest that high intraoperative fill volumes are associated with an increase in perioperative complications, specifically, mastectomy flap necrosis. 9,14 In addition, patients in the inverted-T group demonstrated a higher mean body mass index than the control group (28.7 kg/m 2 versus 26.7 kg/m 2 ; p = 0.04). This would indicate a larger percentage of obese patients in the inverted-T cohort, a factor shown previously to increase complication rates in expander/implant reconstruction.…”
Section: Ementioning
confidence: 88%
See 1 more Smart Citation
“…Although this may allow for better skin recruitment, some studies suggest that high intraoperative fill volumes are associated with an increase in perioperative complications, specifically, mastectomy flap necrosis. 9,14 In addition, patients in the inverted-T group demonstrated a higher mean body mass index than the control group (28.7 kg/m 2 versus 26.7 kg/m 2 ; p = 0.04). This would indicate a larger percentage of obese patients in the inverted-T cohort, a factor shown previously to increase complication rates in expander/implant reconstruction.…”
Section: Ementioning
confidence: 88%
“…3,5,7,8 Variability in reported necrosis rates may depend not only on differences in surgical technique but also on the authors' definition of what constitutes tissue necrosis. 9 Our definition of flap necrosis was all-inclusive, ranging from simple epidermolysis to extensive fullthickness skin loss.…”
Section: E Discussionmentioning
confidence: 99%
“…These factors were determined a priori based on literature review and surgeon experience and included age older than 65 years, body mass index greater than 30, active smoking, history of preoperative radiation therapy, mastectomy weight greater than 800 g, Wise-pattern incision, nipple-sparing mastectomy, and direct-to-implant reconstruction. [5][6][7][8][9][10][11][12][13] We also performed an exploratory analysis of whether the effect of nitroglycerin varied according to the number of risk factors. A score of 1 was given for each of the aforementioned risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…815 The literature is inconsistent due to differing definitions of skin flap necrosis and variable patient selection criteria. Studies have shown many factors to be associated with skin flap necrosis including smoking 9,13,14,16 , obesity 8,9,12,14,15,1719 , incision type 11,2022 , age 14,1618 , hypertension 14,18 , tumescence 1618 , volume of tissue expander fill 17,18 , and larger breasts. 8,23 To address the limitations in the literature, we designed a prospective study to determine the rate of skin flap necrosis after mastectomy with reconstruction and to identify potentially modifiable factors that could improve patient selection and outcomes.…”
Section: Introductionmentioning
confidence: 99%